Perlindungan Konstitusional State Auxiliary Agencies Berbasis Independent Regulatory Agencies (IRAS) Guna Mewujudkan Kredibilitas Pelayanan Negara Secara Demokratis Dalam Perspektif Check And Balances - Nur Afaricha Aylinda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article will discuss the concept of Independent Regulatory Agencies (IRAs) as an alternative to constitutional protection for c in Indonesia. State auxiliary agencies are state institutions that are formed and have authority based on other laws and regulations. In Indonesia, state auxiliary agencies are not regulated in a legal basis, so it is still unclear about their position in the constitution. Apart from that, there is still uncertainty regarding the independence of state auxiliary agencies which causes the authority of these state institutions to be limited. This study is a qualitative legal research. Data collection techniques using literature study. The type of data used is secondary data derived from data sources of laws and regulations, articles, and journals. The research method used is a normative juridical approach. Data analysis techniques use descriptive analysis specificatios. This research finds that state auxiliary agencies in Indonesia were formed on the basis of other laws or are said to be not state institutions that have the authority mandated by the 1945 Constitution. Unlike in the United States and Europe, state auxiliary agencies are legally guaranteed by laws and regulations and are even stated explicitly and limitively. Independence and self regulatory are two important elements in IRAs. This study recommends the concept of IRAs as an idea for improving the arrangement of state auxiliary agencies in Indonesia so as to create effective democratic state services. Some of the models that can be applied include; minimizing the authority of the DPR in selecting leaders of state auxiliary agencies, granting independent authority and affirming non-partisan provisions.